International humanitarian law tested by armed conflicts in Africa: examples from the countries of the Lake Chad Basin Commission (LCBC). - (:unkn) unknown (My University, 2023)
Armed conflicts today constitute one of the major challenges for LCBC States. Indeed, for decades, this area has experienced an increase in armed conflicts of all kinds. This situation has led state, regional and international actors to put in place mechanisms that can contain these conflicts under the framework of international humanitarian law.As such, legal instruments and institutional mechanisms are implemented. These mechanisms for framing international humanitarian law contribute to the circumscription of armed conflicts for the respect of human rights. However, they alone were not enough to limit respect for human rights during armed conflicts in LCBC countries.The atrocities during these armed conflicts in this aforementioned area demonstrate the weaknesses and failures of normative and institutional mechanisms. Thus, the need to readjust these mechanisms is essential. This is achieved through a real readjustment of normative and institutional frameworks. In this sense, the normative strengthening of international humanitarian law, the promotion of democracy and the consolidation of the institutional architecture of humanitarian organizations constitute essential conditions for effectively initiating respect for human rights and international humanitarian law during armed conflicts in LCBC countries.
Keywords: African Research